"Supreme in Ruin": Empire's Afterlife in Romantic Encounters with Imperial Ruins. Issue 2 (4th March 2021) - Camoglu, Arif
ABSTRACT: Registered in Romantic depictions of imperial ruins is the endurance of empire in its immateriality: the imageries of empire's ruination announce a future where imperial sovereignty maintains its presence spectrally. Using Jacques Derrida's notion of hauntology, and recruiting further insight from political theory, this essay argues that empire manifests in Romantic vision as an ontological dynamic, that is, an obscured yet efficacious force that impinges on the subject's relationship with the world. My discussion traces this abstraction of power in the works of Felicia Hemans, Lord Byron, Mary Shelley, Anna Laetitia Barbauld, and Robert Southey, clustered together through their mutual influence and shared source, Edward Gibbon's The History of the Decline and Fall of the Roman Empire . In the light of these authors' reflections on the ruins of empire, this article focuses the ontological dimension of imperial sovereignty to extend the critique of imperialism in Romantic studies beyond its familiar historical-material terrain, toward sites where empire prevails even after its presumed disintegration as an official, political entity.